The Relationship Between The Level of Knowledge About Hypertension and The Behavior of Preventing Complications in Hypertension Patients in The Area of RT 06 RW 005, Pinang Ranti Village - Kusnanto Kusnanto; Hanif Ahmad Nurdien (Jurnal Ners, 2026)
Hypertension is a major global public health concern because it is a non-communicable disease, also known as a silent killer, and the number one killer worldwide. Hypertension can be attributed to the tip of the iceberg, a typical phenomenon of society. One in three people suffer from hypertension, and this figure continues to rise every year. According to the World Health Organization (WHO), 1.4 billion adults aged 30–79 worldwide suffer from hypertension. Knowledge influences efforts to improve behaviors to prevent complications from hypertension. A lack of understanding of the consequences of hypertension can influence behaviors aimed at preventing complications, as evidenced by persistent consumption of fatty foods, lifestyle changes, smoking, consumption of high-cholesterol foods, inappropriate stress management, alcoholic beverages, and obesity. The purpose of this study was to determine the relationship between knowledge about hypertension and behaviors to prevent complications among hypertension sufferers in RT 06 RW 005, Pinang Ranti Village. Research Method: This study used a quantitative design with a cross-sectional method. The sample in this study was determined using a total sampling technique, with 50 respondents. Research Results: Statistical test results showed a Pearson Chi-Square value of 55.917 with a significance value (p-value) of 0.000. A p-value <0.05 indicates a significant relationship between knowledge level and preventive behavior. Conclusion: There is a significant relationship between knowledge level and preventive behavior. The higher the respondent's knowledge level, the better the preventive behavior .